Erythromelalgie: rote Haut und Schmerz - Dusch, Martin; Schmelz, Martin (Der Schmerz, 2019)
Erythromelalgia is a rare disease that is associated with hemato-oncological diseases or after taking certain drugs and toxins, but it can also occur as an independent clinical picture, for example, due to mutations in the sodium channel NaV1.7. Clinically, there is a characteristic triad of attack-like burning pain and skin redness in the area of the distal extremities, which can be alleviated by excessive cooling. The attacks are triggered by heat, exertion, and stress. The diagnosis is primarily made clinically and can be confirmed by genetic testing if a sodium channel NaV1.7 mutation is present. Important differential diagnoses are complex regional pain syndrome, the non-freezing cold injury, and small fiber neuropathies. Therapy is multidisciplinary and has to be planned individually and include physical therapy and psychotherapy as well as drug therapy as integral components.
Gesehen am 25.10.2019